Synaptic regulation of the hypothalamic–pituitary–adrenal axis and its modulation by glucocorticoids and stress - Levy, Ben; Tasker, Jeffrey (Frontiers in Cellular Neuroscience, 2012)
Dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis has been implicated in a range of affective and stress-related disorders. The regulatory systems that control HPA activity are subject to modulation by environmental influences, and stressful life events or circumstances can promote subsequent HPA dysregulation. The brain is a major regulator of the HPA axis, and stress-induced plasticity of the neural circuitry involved in HPA regulation might constitute an etiological link between stress and the development of HPA dysregulation. This review focuses on the synaptic regulation of neuroendocrine corticotropin-releasing hormone (CRH) neurons of the hypothalamic paraventricular nucleus, which are the cells through which the brain predominantly exerts its influence on the HPA axis. CRH neuronal activity is largely orchestrated by three neurotransmitters: GABA, glutamate, and norepinephrine. We discuss our current understanding of the neural circuitry through which these neurotransmitters regulate CRH cell activity, as well as the plastic changes in this circuitry induced by acute and chronic stress and the resultant changes in HPA function.